2019
DOI: 10.1002/tafs.10176
|View full text |Cite
|
Sign up to set email alerts
|

Winter Survival, Habitat Use, and Hypoxia Tolerance of Montana Arctic Grayling in a Winterkill‐Prone Lake

Abstract: Winter hypoxia in shallow, ice‐covered lakes can be a significant limiting factor for overwintering fish populations. In this study we tested the hypothesis that low overwinter survival due to winter hypoxia is a limiting factor for a rare, adfluvial population of native Arctic Grayling Thymallus arcticus inhabiting Upper Red Rock Lake, Montana. We used a combined laboratory and telemetry study to document the extent of hypoxia over two winters and to assess the physiological tolerance, behavioral response, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…Upper Red Rock Lake, which is used by the fish during the remainder of year, is a shallow (<2 m deep), highelevation lake, where winter hypoxia is a concern for Arctic Grayling survival due to 7 months of ice cover (Davis et al 2019). Areas with sufficient dissolved oxygen for overwinter survival may be reduced in some years (Davis et al 2019), leading to increased competition for food resources. Cutting et al (2016) found that Arctic Grayling in Upper Red Rock Lake fed on similar food sources as nonnative trout (Brook Trout Salvelinus fontinalis and hybrid trout [Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri × Rainbow Trout O. mykiss]), potentially leading to competition for food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper Red Rock Lake, which is used by the fish during the remainder of year, is a shallow (<2 m deep), highelevation lake, where winter hypoxia is a concern for Arctic Grayling survival due to 7 months of ice cover (Davis et al 2019). Areas with sufficient dissolved oxygen for overwinter survival may be reduced in some years (Davis et al 2019), leading to increased competition for food resources. Cutting et al (2016) found that Arctic Grayling in Upper Red Rock Lake fed on similar food sources as nonnative trout (Brook Trout Salvelinus fontinalis and hybrid trout [Yellowstone Cutthroat Trout Oncorhynchus clarkii bouvieri × Rainbow Trout O. mykiss]), potentially leading to competition for food.…”
Section: Discussionmentioning
confidence: 99%
“…Areas with sufficient dissolved oxygen for overwinter survival may be reduced in some years (Davis et al. 2019), leading to increased competition for food resources. Cutting et al.…”
Section: Discussionmentioning
confidence: 99%
“…The upper meter, by contrast, was a comparatively dynamic layer, exhibiting a range of DO concentrations from * 0 to 10 mg/l. DO concentrations \ 4 mg/l were considered hypoxic in this situation because these DO concentrations in this range elicited stress responses (behavioral avoidance and increased opercular beats) and decreased survival in juvenile and adult Arctic Grayling in laboratory experiments whereas such impairments were absent at higher DO levels (Davis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important implications for measuring the dynamics of winter hypoxia and estimating its impacts on overwintering fishes. In Upper Red Rock Lake, the inlet tributary mouths likely offer DO refugia key for survival of grayling and other species during winters with otherwise widespread hypoxic conditions (Gangloff, 1996;Davis et al, 2019). Identification of such refugia will help conserve these critical habitats (Weber et al, 2013;Tibbles et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that hypoxia caused the die‐off at Shaviovik Spring, as (1) ice cover prevents the dissolution of atmospheric oxygen (Kirillin et al, 2012), making dissolved oxygen (DO) a broad wintertime constraint on habitat quality for Arctic freshwater fish (Leppi et al, 2016), and (2) DO measured in at least some ice‐covered Arctic pools elsewhere has been lower than the lethal threshold of Arctic grayling (0.75 mg/L or 6% saturation at 3°C for adults; Davis et al, 2019), including at sites with documented fish mortality (Bendock & Burr, 1984; Leppi et al, 2016; Schmidt et al, 1989). We acknowledge that water from Arctic perennial springs can be high in DO (Childers et al, 1977).…”
Section: Figurementioning
confidence: 99%